KEEFEKTIFAN FORMULASI BAKTERI BURKHOLDERIA CEPACIA ISOLAT E76 TERHADAP RHIZOCTONIA SOLANI KÃ¼HN PADA PERTUMBUHAN TANAMAN PADI DI LABORATORIUM - Wartono, Wartono; Suryadi, Yadi; Susilowati, Dwi Ningsih (JURNAL AGROTROPIKA, 2012)
In vitro study was carried out to test the effectiveness of the formulation containing Burkholderia cepacia isolates E76 in suppressing growth of Rhizoctonia solani and its effect on plant growth. The study was conducted at Plant Disease Laboratory, Indonesian Center for Agricultural Biotechnology and Genetic Resources Research and Development Bogor, in January to July 2012. The in vitro method was done by growing the bacteria B. cepacia isolates E76 together with R. solani in one dish of potato dextrose agar (PDA) medium. Seed of ?Ciherang? rice was treated with formulation of B. cepacia isolates E76. Observation were done to relative inhibitory rate, rice germination, shoot length, and root length. Results showed that B. cepacia isolates E76 formulation was effective in suppressing the growth of R. solani with relative inhibitory rate at 24 and 48 hour after incubation, respectively 31,3 ? 60,2% and 28,9 ? 47,8%. Rice germination and growth on treated rice seeds were better than control treatment. Concentration at 3% concentration was suggested to be used as recommended concentration for further testing. Key words: Formulation, Burkholderia cepacia isolat E76, Rhizoctonia solani